2014
DOI: 10.1098/rsbl.2013.1024
|View full text |Cite
|
Sign up to set email alerts
|

Red trap colour of the carnivorous plant Drosera rotundifolia does not serve a prey attraction or camouflage function

Abstract: The traps of many carnivorous plants are red in colour. This has been widely hypothesized to serve a prey attraction function; colour has also been hypothesized to function as camouflage, preventing prey avoidance. We tested these two hypotheses in situ for the carnivorous plant Drosera rotundifolia. We conducted three separate studies: (i) prey attraction to artificial traps to isolate the influence of colour; (ii) prey attraction to artificial traps on artificial backgrounds to control the degree of contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…It might be changes in any or a number of these mechanisms that result in the observed differences in prey capture. There is no evidence as yet that D. rotundifolia actually attracts prey (Foot et al 2014); but investment in prey capture (through the production of sticky mucilage) is reduced when root N availability is increased experimentally (Thorén et al 2003), which might be the mechanism here. Such a reduction in investment in prey capture has not been demonstrated in-situ for D. rotundifolia but has been shown for Sarracenia purpurea by Ellison and Gotelli (2002).…”
Section: Discussionmentioning
confidence: 93%
“…It might be changes in any or a number of these mechanisms that result in the observed differences in prey capture. There is no evidence as yet that D. rotundifolia actually attracts prey (Foot et al 2014); but investment in prey capture (through the production of sticky mucilage) is reduced when root N availability is increased experimentally (Thorén et al 2003), which might be the mechanism here. Such a reduction in investment in prey capture has not been demonstrated in-situ for D. rotundifolia but has been shown for Sarracenia purpurea by Ellison and Gotelli (2002).…”
Section: Discussionmentioning
confidence: 93%
“…In more open areas, the plants might be more apparent and so more likely to be seen by herbivores. Foot et al (2014) found that, in a study of prey capture by D. rotundifolia, fewer insects were attracted to red artificial leaves than to green artificial leaves. This might indicate that insects are deterred by red coloration.…”
Section: An Alternative and Intriguing Hypothesis Is That Leaf Rednesmentioning
confidence: 97%
“…Like many carnivorous plants, the leaves of D. rotundifolia have a distinctive red coloration, due to the presence of anthocyanins (Egan & der Kooy, 2013). This red colour was thought to serve a prey attraction function (Ichiishi et al, 1999;Lloyd, 1942), but experimental studies have shown this not to be the case (Foot, Rice, & Millett, 2014). Alternative hypotheses for the functional role of leaf reddening are as a protection against excess light and UV-B radiation, herbivory defence or osmotic adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…But what about flypaper plants with adhesive traps? Would they merely function as passive insect traps whose efficiency is determined by shape, size, and orientation (e.g., Karlsson et al, 1987; Foot et al, 2014)?…”
mentioning
confidence: 90%